THE EFFECT OF OCCUPATIONAL GARDENING THERAPY ON BLOOD PRESSURE AND ANXIETY OF ELDERLY HYPERTENSION IN BADUNG - Martini, Ni Made Dwi Ayu; Sari, Ni Luh Putu Dian Yunita; Darmaja, Ketut (E-Jurnal Medika Udayana, 2025)
Controlling blood pressure and anxiety is essential for the elderly with hypertension. This can impact their physical, psychological, and social well-being. Lifestyle modifications are recommended for people with hypertension, and one of these interventions is occupational gardening therapy. Occupational gardening therapy at home involves engaging the elderly in activities such as planting and tending to plants. This study aims to determine the effect of occupational gardening therapy on blood pressure and anxiety in the elderly with hypertension. The research methodology employed was quantitative with a pre-experimental one-group pretest-posttest design. The study includes a total of 30 elderly participants who met eligibility criteria using purposive sampling techniques. Research instruments used consist of questionnaires, a sphygmomanometer, and a stethoscope, supplemented with standardized operational procedures of occupational gardening therapy and measuring blood pressure. Paired t-test analysis indicates that there is an effect of occupational gardening therapy on blood pressure and anxiety in the elderly with hypertension (p<?). In collaboration with community health workers, primary health care nurses can offer guidance for implementing home-based occupational gardening therapy as an alternative complementary treatment for elderly with hypertension to control blood pressure and anxiety.